The Effect of Audit Fee, Audit Tenure, KAP Reputation, and Audit Rotation on Audit Quality in Transportation Companies Listed on the Indonesia Stock Exchange - Arie Pratania Putri; Mey Sari Simbolon; Sylka Erlikasna Surbakti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Transportation companies is a company whose activities are engaged in the field of goods or human transportation services from the initial place of transportation until the place where the transportation activity stops. This study aims to determine the relationship between audit fees, audit tenure, hood rotation, and audit rotation on audit quality in transportation companies listed on the Indonesian stock exchange with the official website www.idx.co.id Associative research method with quantitative approach. The population of this analysis is 22 companies with a research period of 3 years. Therefore, the number of samples is 66 companies. The technique used in the research that has been tested shows that variables with the greatest significance are audit fees, audit rotation, hood reputation, and audit tenure on audit quality. The data was also processed with the help of SPSS version 20 program with logistic linear regression technique.